2010
DOI: 10.1016/j.matdes.2009.08.031
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the mechanical behaviour of self-piercing riveted and resistance spot welded aluminium sheets for the automotive industry

Abstract: Abstract:The increased application of lightweight materials, such as aluminium has initiated many investigations into new joining techniques for aluminium alloys. The Resistance Spot Welding (RSW) concept for aluminium has always attracted many researchers from different organizations. Selfpiercing riveting (SPR) is the major production process used to join aluminium sheet body structures for the automotive industry. The research team at the University Of Warwick has investigated these two major joining techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(45 citation statements)
references
References 9 publications
1
41
0
3
Order By: Relevance
“…Their results showed that the SPR joints had similar or better lap shear and T-peel strengths than the equivalent RSW joints. Further research from Han et al [113] showed that the strength of SPR joints and RSW joints was material stack and process parameters related. Their results showed that when different joint stacks were studied or when different process parameters were used, the static strength of the SPR joints could be higher or lower than that of the RSW joints, but generally speaking, SPR joints had a better T-peel strength and RSW joints had a better cross-tension strength, which matched well with the results from Doo [7].…”
Section: Comparison Of Spr Joints With Joints From Other Processesmentioning
confidence: 99%
“…Their results showed that the SPR joints had similar or better lap shear and T-peel strengths than the equivalent RSW joints. Further research from Han et al [113] showed that the strength of SPR joints and RSW joints was material stack and process parameters related. Their results showed that when different joint stacks were studied or when different process parameters were used, the static strength of the SPR joints could be higher or lower than that of the RSW joints, but generally speaking, SPR joints had a better T-peel strength and RSW joints had a better cross-tension strength, which matched well with the results from Doo [7].…”
Section: Comparison Of Spr Joints With Joints From Other Processesmentioning
confidence: 99%
“…[1] Although widely used to weld steel sheet, resistance spot welding (RSW) is more difficult to apply to light alloys because of their high conductivity, low strength at elevated temperature, and tendency to degrade the electrodes. [2,3] Furthermore, alternative point joining processes like self-piercing rivets [4][5][6] have high consumable costs. FSSW has already been applied successfully in automotive manufacturing by the Mazda Motor Corporation, which claims large energy and capital investment gains compared with RSW (~90 pct energy savings and 40 pct investment reduction [1] ).…”
Section: Introductionmentioning
confidence: 99%
“…Riveting; SPR) 6,7) , 마찰교반점접합(Friction Stir Spot Welding, 이하 FSSW로 표기) 8 , 전 세계적으로 주목을 받아, 이에 대한 연구 및 개발이 활발히 진행되고 있다 [8][9][10] .…”
Section: 서 론unclassified